Romania : Transport Sector Rapid Assessment - World Bank (Washington, DC, 2014)
The Europe 2020 strategy and the legislative package from the European commission provide European Union (EU) member states a framework and means for moving towards a greener and more competitive low carbon economy that makes efficient use of resources and is resilient to climate risk. The integration of both mitigation and adaptation actions into Romania's national policies, programs, and strategies will be a critical step in shifting its development path towards a climate resilient, low carbon, and green economy. In this context, the Government of Romania has requested the World Bank to provide advisory services on climate change, including operationalizing its national climate change strategy and action plan, identifying and integrating climate-related actions in new operational programs, building a solid analytical base for impact assessment and climate-related decision making, and enhancing climate-friendly practices and monitoring system. This report is a deliverable under component B of the advisory services; support the preparation of the climate change-related actions under the 2014-2020 operational programs. This report presents the results of the rapid assessment process for the transport sector. This includes both general transports (which previously fed into the sector operational program for transport (SOP-T) and urban transport (which previously fed into the regional operational program (ROP).